Community pharmacy Medicines Use Review: current challenges - Latif A (Dove Medical Press, 2018)
Asam Latif School of Health Sciences, Queen’s Medical Centre, The University of Nottingham, Nottingham, UK Abstract: With a growing aging population, the appropriate, effective, and safe use of medicines is a global health policy priority. One concern is patients’ non-adherence to medicines, which is estimated to be up to 50%. Policymakers seek to reconfigure medicine management services and consider community pharmacy as especially well-placed to improve medicine use. In England and Wales, a commissioned medication review service called “Medicines Use Reviews (MURs)” was made available in through the National Health Service (NHS) in 2005. This involves a patient–pharmacist consultation to improve patients’ knowledge and the use of medicines and to help reduce avoidable waste. However, over a decade since their introduction, questions remain over the extent to which the MUR policy has successfully been embedded in practice and translated into more effective use of medicines. The MUR intervention continues to hold many challenges ranging from poor public awareness and acceptance of MURs, organizational constraints, and issues over interprofessional collaboration. Many of these challenges are not exclusive to the MUR service, or even to the community pharmacy setting. Nevertheless, by identifying and exposing such challenges, an opportunity exists for policymakers and commissioners to seek to improve this service to patients. This narrative review explores the current challenges that face MURs. Damschroder et al’s consolidated framework for implementation research is employed to help organize these challenges from patient and professional perspectives across multiple contexts. Over the past decade, MUR policy and practice has continued to evolve, being shaped by research, organizational and professional influences, and policy. Reforms to the service suggest that the MURs are becoming more responsive to patients’ need and preferences. It is intended that this review will create impetus and scope for further debate, service reconfiguration, and ultimately service improvement. Keywords: adherence, community pharmacy, medicines management, Medicines Use Reviews, pharmacist, implementation research, medicines optimization